Analysis of morphology, cytotoxicity, and water content characteristics of freeze-dried amnion membrane from human and bovine - Suroto, Heri; Pratamanugroho, Ilham; Prajasari, Tabita; Susilowati, Helen; Khang, Gilson (Narra Sains Indonesia, 2024)
Placenta tissue has biological advantages, including anti-inflammatory, anti-bacterial, anti-fibrotic formation, and immunomodulatory properties. The amnion membrane (AM) is an inner side membrane of the placenta that faces the fetus. The main sources of amnion are humans and animals, with bovine being one of the significant sources. The aim of this study was to analyze the morphology, cytotoxicity, and water content characteristic of freeze‑dried amnion membrane (FD‑AM) from humans and bovines to measure the safety and compatibility of bovine FD-AM as an alternative to human FD-AM. This study is an observational cross-sectional study. Samples were divided into two groups: human FD-AM and bovine FD-AM groups. Both groups were examined for morphology characteristics by scanning electron microscopy (SEM), cytotoxicity by 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide (MTT) analysis, and water content by drying through moisture analyzer device. The morphology characteristics of bovine FD-AM and human FD-AM, as observed through SEM, showed similar results of a smooth, flat surface with no cavity and were well dehydrated. MTT assay analysis on both groups demonstrated cytocompatibility with cell viability exceeding 70% in the control group. However, human FD-AM showed a higher number of viable cells (0.19±0.01) compared to bovine FD-AM (0.12±0.03), with a statistically significant difference (p<0.05). The water content analysis revealed that both groups met the standard, with levels below 10%. While bovine FD-AM (7.19±0.45%) had slightly higher water content than human FD-AM (6.79±1.0%), the difference was not significant (p>0.05). Both human FD-AM and bovine FD-AM showed good results in morphology, cytotoxicity, and water content characteristics and compatibility. In conclusion, bovine FD-AM might be considered as an alternative to human FD-AM.